2021
DOI: 10.1093/cid/ciab464
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Readmission in the United States Following Hospitalization With Coronavirus Disease 2019

Abstract: Background Patients hospitalized for COVID-19 may experience complications following hospitalization and require readmission. This analysis estimates the rate and risk factors associated with COVID-19-related readmission and inpatient mortality. Methods This is a retrospective cohort study utilizing deidentified chargemaster data from 297 hospitals across 40 US states on patients hospitalized with COVID-19 February 15-June 09… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
4
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 22 publications
2
39
4
4
Order By: Relevance
“…The COVID-19 pandemic brought new challenges to the general population and even more so to patients with end-stage renal disease (ESRD), many of whom have comorbidities now acknowledged as risk factors for severe COVID-19 [ 5 ]. Aside from the logistic challenges summarized elsewhere [ 6 ], these patients, both dialysis-treated and kidney transplant patients, face morbidity and mortality risks that are significantly higher than the general population [ 7 , 8 ]. Unfortunately, it is known from existing vaccine preparations such as anti-hepatitis B virus and influenza [ 9 12 ], that both dialysis and kidney transplant patients require higher doses and repeat inoculations (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic brought new challenges to the general population and even more so to patients with end-stage renal disease (ESRD), many of whom have comorbidities now acknowledged as risk factors for severe COVID-19 [ 5 ]. Aside from the logistic challenges summarized elsewhere [ 6 ], these patients, both dialysis-treated and kidney transplant patients, face morbidity and mortality risks that are significantly higher than the general population [ 7 , 8 ]. Unfortunately, it is known from existing vaccine preparations such as anti-hepatitis B virus and influenza [ 9 12 ], that both dialysis and kidney transplant patients require higher doses and repeat inoculations (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…A study with more than 29,000 patients who had confirmed COVID-19 reported the length of hospitalization time as 8 days 13 . A Korean study reported the length of hospitalization due to COVID-19 as 17 days 14 .…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic brought new challenges to the general population and even more so to patients with end-stage renal disease (ESRD), many of whom have comorbidities now acknowledged as risk factors for severe COVID-19. Aside from logistic challenges summarized elsewhere 3 , these patients, both dialysis-treated and kidney transplant patients, face morbidly and mortality risks that are significantly higher than the general population 4, 5 . Unfortunately, it is known from existing vaccine preparations such as anti-hepatitis B virus and the influenza 6-9 , that both dialysis and kidney transplant patients require higher doses and repeat inoculations (i.e.…”
Section: Introductionmentioning
confidence: 99%